Effects of Audition Programs on Viewing Satisfaction: Meta-Analysis Methodology - Qilin Wang; Seungyon-Seny Lee (Migration Letters, 2023)
The controversial results of studying existing audition programs were quantitatively integrated and analyzed, and the empirical study data on viewers’ satisfactions were reanalyzed in this paper. The study applied meta-analysis to interpret viewing satisfactions of audition programs and demographic correlations based on these results. The data of this study had been retrieved 929 articles and were collected from the database of the Korea Academic Research Information Service. The keywords of research subjects were set up as ‘viewing satisfaction’, ‘audition program’, ‘idol audition program’, and ‘music audition program’. After evaluating the accuracy of their data or their correspondence to the subjects of this study, a total of 16 theses were selected and analyzed. An analysis of the correlation between ’Age-Viewing satisfaction’ and ’Educational background-Viewing satisfaction’ showed that a few study papers belonging to small groups might affect heterogeneity inspection. Further, based on the effect size of subgroup analysis, we could not assume statistically different effects. Accordingly, we could find that the viewing satisfactions of audition programs were slightly higher in female than male. The satisfactions were varied according to age groups - the highest in 20s, then higher in 30s, in 40s, and in 10s. In addition, viewing satisfaction was not related to educational background, and their impact on viewing satisfaction of programs differed according to inspection method.